Biologia reprodutiva da caraúna marrom Acanthurus chirurgus (Bloch, 1787) (Perciformes: Acanthuridae) capturada pela frota artesanal no Litoral Norte do estado de Pernambuco, Brasil - ALMEIDA, Paulo Rogério de Souza (2020)
The aim of the present study was to describe the dynamics oogenesis, spermatogenesis process from macroscopic and microscopic analyzes and reproductive biology from Acanthurus chirurgus based in the gonadosomatic index, description, distribution of the maturation stages, seasonal variation of the maturation stages, first maturation size, frequency and spawning type, batch fecundity, relative and fecundity type and to evaluate the influence of rainfall and temperature in the reproductive cycle. Between may 2016 and may 2018, 317 males and 188 females were analyzed (n = 505), from the landings of artisanal fishing boats that operate with traps on the Island Itamaracá, Pernambuco, Brazil. The length ovaries varied from 1.12 to 6.36 cm and 0.13 to 2.72 cm from width and weight varied from 0.05 to 9.52 g. Ovaries are constituted by smooth muscle tissue, lamellas ovigerous, follicular and germinative cells (oogonia, primary growth oocytes – with nucleolar chromatin, cortical alveoli, vitellogenic I, II, III, germinal vesicle migration and breakdown and hydration oocyte form the ovarian complex. The length testis varied from 0.86 to 3.81 cm and 0.02 to 1.27 cm from width. The weight varied from 0.001 to 4.30 g. The testis are unrestricted spermatogonial type, constituted by smooth muscle tissue, theca and granulosa cells, radiate zone (external, intermediate, internal), tunica albuginea, primary and secondary seminiferous tubes, sperm duct and interstitial tissue, form the testicular complex. No significant statistical differences from stages: development, regressing and regenerating for length and width of the ovaries and testis. A higher frequency of females and males was observed in the 23˧25 and 25˧27 cm classes. The growth was negative allometric β1 = 0.139 and the sex ratio was (0.6F: 1M). Both sexes were classified into six stages of development: females - immature, developing, spawning capable, actively spawning, regressing and regenerating and males – immature, developing, able to release, releasing, regressing and regenerating. Greater reproductive intensity occurred from August to December (dry period – average rainfall: 90.5 mm), with greater frequency of ovaries in the regressing and regenerating stages. In the PCA, rainfall of 62.6% and the period of 34.8%, had a greater influence on the stages of ovarian development, with no significant statistical differences between the groups: spawning capable and actively spawning (p = 0.548), developing and regressing (p = 0.229). The minimum (L50) and maximum (L99) maturation sizes were (18.03 and 22.05 cm - R² = 0.91). The average spawning frequency varied from 36.2% to 38.7%, with a potential spawning frequency/day/ year of 2.7 and 2.5 and 19 and 18, using the OH and POF method, respectively. Potential fecundity ranged from 15,962 to 75,880 (36,715 ± 14.9), batch and relative fecundity ranged from 2,801 to 10,774 (6,622 ± 6.62) and 0.6 to 0.19 (0.12 ± 0.03) oocytes per milligram of female weight. A gap in the group of oocytes with diameter at around 325 μm was observed in the Vtg III phase, separating the group of less developed oocytes from the modal group of oocytes more developed in the GVM and GVBD phases in the 375-425 μm class, corresponding to the group of oocytes that will be released. The diameter of the oocytes corresponding to the spawning capable stage varied from 27.7 to 600 μm (139.36 ± 123.41), with multimodal distribution, with a decrease in the 400-450 μm range. The pattern of development and recruitment of oocytes is clearly observed throughout the study period. The distribution of the oocyte size frequency for each stage of ovarian development, without the presence of a gap in the diameter of the oocytes in primary and secondary growth, may be indicative of indeterminate fecundity, with cyclic oocyte development. Females can spawning more than two times during the reproductive season, with the spawning "synchronous in more than two groups". In the males the maturation process is not continuous, since showed testicles in the regeneration stage.